DNMT1 and DNMT3b cooperate to silence genes in human cancer cells - Rhee, Ina; Bachman, Kurtis E.; Park, Ben Ho; Jair, Kam-Wing; Yen, Ray-Whay Chiu; Schuebel, Kornel E.; Cui, Hengmi; Feinberg, Andrew P.; Lengauer, Christoph; Kinzler, Kenneth W.; Baylin, Stephen B.; Vogelstein, Bert (Nature (London), 2002)
Inactivation of tumour suppressor genes is central to the development of all common forms of human cancer. This inactivation often results from epigenetic silencing associated with hypermethylation rather than intragenic mutations. In human cells, the mechanisms underlying locus-specific or global methylation patterns remain unclear. The prototypic DNA methyltransferase, Dnmt1, accounts for most methylation in mouse cells, but human cancer cells lacking DNMT1 retain significant genomic methylation and associated gene silencing. We disrupted the human DNMT3b gene in a colorectal cancer cell line. This deletion reduced global DNA methylation by less than 3%. Surprisingly, however, genetic disruption of both DNMT1 and DNMT3b nearly eliminated methyltransferase activity, and reduced genomic DNA methylation by greater than 95%. These marked changes resulted in demethylation of repeated sequences, loss of insulin-like growth factor II (IGF2) imprinting, abrogation of silencing of the tumour suppressor gene p16INK4a, and growth suppression. Here we demonstrate that two enzymes cooperatively maintain DNA methylation and gene silencing in human cancer cells, and provide compelling evidence that such methylation is essential for optimal neoplastic proliferation.